Tradisi Haul dan Solidaritas Masyarakat: Studi tentang Tradisi Haul Sesepuh di Desa Sembayat Kecamatan Manyar Kabupaten Gresik - Santria, Aisyah Anggun (Proceedings of Student Symposium on Ushuluddin and Islamic Thought, 2024)
The majority of religions adhered to by the people of Sembayat village are Islam. Judging from their ethnicity, the majority of people are Javanese. The Sembayat community is known for its high level of religious knowledge, which is supported by the existence of various religious traditions so that it is one of the factors supporting the high level of religious knowledge possessed by this community. Tradition is a word that refers to customs or customs that have been passed down from generation to generation or regulations that are implemented by society. Tradition is a cultural heritage that plays an important role in shaping the identity of a community. This research aims to examine traditions and community solidarity in haul events in Sembayat village. This haul tradition has been carried out for years, this haul tradition has been going on for quite a long time and is packaged in various community activities. This research uses qualitative methods to explain how community solidarity and the series of haul events have become a tradition in Sembayat village. The results of the discussion show that hauls have many positive impacts on society, where the haul tradition that is carried out can strengthen community solidarity through the events held. The aim of this research is to find out what the traditions and solidarity of the community are and what the schedule of events in the haul in Sembayat village